ANALYSIS OF POLITICAL DOCUMENTS FORMING THE FRAMEWORKS OF THE NATIONAL SECURITY POLICY OF GEORGIA AND THE RUSSIAN FEDERATION - Ghazaryan, Karen (KATCHAR / ACADEMIA. SOCIAL SCIENCE PERIODICAL, 2025)
In order to understand the foreign policy of Georgia and the Russian Federation, and especially the regional policy, the study of the national security strategies adopted by the government is of great importance. It is important to understand how geopolitical developments have affected the strategies of both countries? In the article, we analyze the national security strategies of Georgia and the Russian Federation, their priorities and the changes that have taken place after geopolitical developments. In the course of scientific work, we have set ourselves the following goals.  To study the national security strategies of Georgia and the Russian Federation,  To analyze the changes that took place after the geopolitical developments, which were included in the strategies of the two countries,  To analyze the strategic approaches of both countries for national security and multilateral policy. During the study, we used the method of document and content analysis, as well as the historical comparative method. Based on the goals set before us, we reached the following conclusions.  The National Security Concept of Georgia does not fully represent the situation that exists in the politics of Georgia.  The main changes in Georgia's strategies are related to Russia, but it does not fully represent the current realities. Current changes in Russia's national security strategies are mainly related to geopolitical developments In strategic approaches, Russia considers relations with the South Caucasus at the regional level. Many of Russias strategic approaches have lost their relevance after the developments related to Ukraine in 2022.